A Robust Smart Window: Reversibly Switching from High Transparency to Angle‐Independent Structural Color Display. (2nd March 2015) - Ge, Dengteng; Lee, Elaine; Yang, Lili; Cho, Yigil; Li, Min; Gianola, Daniel S.; Yang, Shu
<x xml:space="preserve">Abstract</x> A smart window is fabricated from a composite consisting of elastomeric poly(dimethylsiloxane) embedded with a thin layer of quasi‐amorphous silica nanoparticles. The smart window can be switched from the initial highly transparent state to opaqueness and displays angle‐independent structural color via mechanical stretching. The switchable optical property can be fully recovered after 1000 stretching/releasing cycles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>